Putting Agricultural Science and Innovation at the top of the Agenda - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Kanayo F. Nwanze, President, International Fund for Agricultural Development (IFAD) commends FARA for putting Agricultural Science Research and Innovation on the top of the agenda for the last 11 years and the need to keep it top on the agenda. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/